"Chaotic Arrhythmia" During Successful Resuscitation After Ingestion of Yew (Taxus baccata) Needles. Issue 12 (December 2019) - Zutter, Andreas; Hauri, Kathrin; Evers, Katrina S.; Uhde, Sabine; Fassl, Jens; Reuthebuch, Oliver Tobias; Berset, Andreas; Kühne, Michael; Donner, Birgit C.
Abstract : Objective: The study aims to describe the management of a case of life-threatening yew ( Taxus baccata ) intoxication. Background: The needles of the yew tree contain highly cardiotoxic taxines. Intoxication with taxines, typically as part of suicide attempts, may lead to potentially lethal arrhythmias which often require prolonged cardiopulmonary resuscitation and other supportive measures. No specific therapy has been described. In some cases, extracorporeal life support has been used. Case: After an attempted suicide with yew needles and out-of-hospital cardiac arrest, a female adolescent was resuscitated for 6 hours according to Advanced Cardiovascular Life Support guidelines. Complex ventricular tachycardias were treated by repeated direct current shocks and broad complex bradycardia managed with transvenous cardiac pacing. Antiarrhythmic drugs (amiodarone, lidocaine), magnesium sulfate, and supportive measures (intravenous lipids, sodium bicarbonate) were provided. The arrhythmias finally resolved, and the patient did not show any significant neurological or cardiac short-term sequelae after 24 hours. Results: The authors describe the successful management of a case of severe taxine intoxication by prolonged conventional advanced cardiac life support lasting for more than 6 hours. Conclusions: In life-threatening yew intoxication, prolonged cardiopulmonary resuscitation is absolutely essential owing to the long duration of the cardiotoxic action of taxines and can lead to an outcome without cardiac or neurological sequelae.